Game Puzzle Geometris sebagai Media Visual Trauma Healing bagi Anak Korban Banjir di Sumatera Barat - Sumema; Yosse, Sofia; Komalasari; Rotama, Hendra; Purnomo, Eko (Universitas Komputer Indonesia, 2026)
The flood disaster that hit West Sumatra in November-December 2025 not only caused physical damage, but also psychological impacts in the form of trauma in children. Symptoms such as anxiety, sleep disorders, difficulty concentrating, and withdrawal from the social environment. Conventional trauma healing approaches often lack creative elements that are appropriate to the world of children. This study aims to design and test the effectiveness of geometric puzzle games as a trauma healing medium that integrates the principles of Visual Communication Design for child flood victims. Using a qualitative approach with an applied experimental method, this study involved 15 elementary school-aged children divided into three groups. Each group competed to arrange geometric puzzles into three meaningful shapes: butterflies, ships and rockets, with the mechanism of one representative looking at the target shape for 10 seconds and then communicating it to the team. Data were collected through participant observation, interviews, focus group discussions, visual documentation, and reflective journals, then analyzed using thematic analysis. The results of the study showed three main findings: (1) the process of visual creation through arranging puzzles became an effective means of non-verbal emotional expression; (2) successful puzzle completion rebuilds self-efficacy and self-confidence; (3) visual communication mechanisms within groups strengthen social cohesion and peer support post-disaster. This research provides theoretical benefits for the development of design science in the context of psychosocial interventions, as well as practical benefits for trauma healing practitioners and designers of visual design-based therapeutic media for children.